Florescer nas brechas: a educação das relações étnico-raciais nas propostas curriculares de Sergipe - Brasil (2011-2018) - Andrade, Ivana Maria Santana (2025)
This research aimed to understand how the proposal for Education on Ethnic-Racial Relations is presented in the last two curricular documents of Sergipe, namely: the Curricular Reference, from 2011 and the Sergipe Curriculum, from 2018. To this end, we outlined the following specific objectives: to discuss the curriculum and its epistemological aspects; to present Education on Ethnic-Racial Relations and its legal and theoretical frameworks; to describe the organizational structure and conceptual basis of the curricular documents; to highlight aspects that point to the presence or absence of ethnic-racial themes in the curricula; to emphasize the development of pedagogical practices based on the aspects found. The study emerges from reflections that lead us to discuss the need for anti-racist education, as one of the aspects to confront the ethnic-racial violence that permeates Brazilian society. To this end, we based our approach on the assumptions of a qualitative research approach in education, using a case study approach with documentary and bibliographic analysis procedures, in which the curricular documents of Sergipe, as well as other legal contributions that support Education for Ethnic-Racial Relations in Brazil, are observed. By analyzing the curricular proposals, it was possible to see that both bring significant notes on the theme of Erer; however, neither of them fully contemplates Erer due to the principle of transversality, although the effort of one of the documents to include this policy is noted. Furthermore, when observing the information found and the gaps left by the two curricula, we considered the feasibility of flourishing between the gaps (Walsh, 2023) and proposing practical activities that are based on the premises of anti-racism, interculturality, and decoloniality.